A spatial analysis of female street traders in the Bloemfontein Central Business District - Juries, Ingrid Keamogetswe (University of the Free State, 2016)
English: Literature on South African cities has focused on the spatial transformation of South African cities and in particular, South African Central Business Districts (CBDs). A review of the literature suggests that not much empirical evidence exists on understanding the spatiality of informal businesses in the CBD. This study is therefore aimed at identifying and analyzing the spatial patterns of female informal traders operating businesses in the Bloemfontein CBD. Research objectives include the identification of the spatial locations used by female informal traders in the Bloemfontein Central Business District, an exploration of the importance of location to female informal traders in the Bloemfontein Business District and an exploration of the impacts of location to female informal traders in the Bloemfontein CBD. The study made use of multiple research techniques which included semi-structured interviews, plotting female informal traders’ locations using a Global Positioning System (GPS), structured observations and secondary data. Through the application of Cluster Theory and through mapping the locations of the female informal traders in the Bloemfontein, it is clear that there is a clustered spatial pattern of female informal traders in the Bloemfontein CBD. The study also highlighted some of the factors which influenced the clustered spatial patterns of the traders as well as access to customers. The study contributes to the understanding of the importance of location for an informal business and also unpacks some of the implications of clustered spatial patterns. It is, therefore, asserted that spatial patterns of informal trading activities in South African cities are just as important as the patterns of formal businesses.

Afrikaans: Literatuur oor Suid-Afrikaanse stede fokus op die ruimtelike transformasie van Suid- Afrikaanse stede, en meer spesifiek, Suid-Afrikaanse Sentrale Besigheidskerns (SBK’s). ŉ Oorsig van die literatuur het aan die lig gebring dat daar nie veel empiriese bewyse bestaan wat begrip het vir die ruimtelikheid van informele besighede in die SBK nie. Hierdie studie is daarom gerig om die ruimtelike patrone van die “plek van besigheid” van vroulike informele handelaars wat tans in die Bloemfonteinse SBK handel dryf, te identifiseer en te analiseer. Navorsingsobjektiewe sluit in die identifisering van die ruimtelike omgewings van die vroulike informele handelaars wat informele besighede bedryf in die Bloemfonteinse SBK en ŉ ondersoek van die belang en impak van lokaliteit vir vroulike informele handelaars. Die studie het van verskeie navorsingstegnieke gebruik gemaak: semi-gestruktureerde onderhoude; die ruimtelike plasing-bepalings van die vroulike informele handelaars se lokaliteit in hul handelsomgewing deur middel van ŉ Globale Posisioneringstelsel (GPS); gestruktureerde waarnemings; en sekondêre data. Deur toepassing van Klusterteorie en deur middel van die gekarteerde posisionering van die vroulike handelaars, is dit duidelik dat daar ŉ gebondelde ruimtelike patroon van informele handelaars in die Bloemfonteinse SBK ontwikkel het. Die studie het ook sommige van die faktore wat die gebondelde ruimtelike patrone, asook die toegang tot kliënte, aan die lig gebring. Die studie dra by tot ŉ begrip van die belang van lokaliteit vir ŉ informele besigheid en gee meer insig tot die implikasies van gebondelde ruimtelike patrone. Dit waarom gestel dat die ruimtelike patrone van informele handelsaktiwiteite in Suid-Afrikaanse stede net so belangrik is as die handelsposisioneringspatrone van formele besighede.
Keywords: Informal sector; Female informal traders; Cluster Theory; Spatial patterns; Central Business District; Informal sector (Economics) -- South Africa -- Bloemfontein; Street vendors -- South Africa -- Bloemfontein; Dissertation (M.A. (Geography))--University of the Free State, 2016